Causal dynamics of poverty reproduction in EU countries. (4th November 2018) - Papanastasiou, Stefanos; Papatheodorou, Christos
Abstract : This study investigated causal mechanisms of poverty reproduction in EU countries by placing emphasis on the parental background effect on sons' poverty risk after having controlled for endogeneity among observable and non‐observable effects of the involved mechanisms. The countries under investigation were old EU member states representing the four welfare regimes in the EU. Having employed path models and utilised EU‐SILC 2005 data, the analysis yielded no statistically significant direct effect of parental background on sons' poverty risk in Denmark. Greece, however, exhibited a statistically significant and quite strong direct effect. Germany and the United Kingdom stood in‐between. Moreover, the analysis found indirect channels through which the parental background affects sons' poverty risk. These findings are expected to enrich the academic discourse and inform the policy‐making process on poverty reproduction and social protection in the EU.